Analisis Catatan atas Laporan Keuangan pos aset tetap pada Badan Keuangan dan Aset Daerah Kota Manado - Siagian, Timotius; Budiarso, Novi Swandari; Kapojos, Peter M. (Yayasan Widyantara Nawasena Raharja, 2025)
Presenters of financial reports must include notes as an integral part of general-purpose financial reports. This study discuss Government Regulation (PSAP) Number 71 Year 2010, Statement number 04 about Notes to the Financial Statements, focusing on the fixed assets account.The objectives of this research are to ascertain the level of detail and clarity of the notes on financial reports for fixed assets items presented by the Finance and Asset Management Agency Regions (BKAD) of the Manado City Government for users of financial reports, including the government and the public.The research method is descriptive qualitative, with data collection through interview techniques and documentation. The research results show that the Notes to Financial Reports, especially fixed asset items produced by the BKAD of the Manado City Government, are not fully informative.